The effect of luminance contrast between sign and surrounding object on gaze behavior: A study in virtual metro station environment with rendered static/dynamic panorama - Ai, Xiaoqun; Liu, Yufei; Wu, Zhendong; Chai, Jingchun; Ju, Xinping; Duan, Wenxiang; Zhao, Lintao; Liang, Ying (Informatica, 2021)
This paper investigated the effect of luminance contrast between sign and surrounding object on the gaze behavior of pedestrian, static or dynamic 360° panorama rendered in a virtual environment applied to simulate the wayfinding of pedestrians in the metro stations. Fifty-five participants observed the sign posters and the advertisement boards with distinct luminance contrasts (31 of them were in static levels, 24 of the rest were in dynamic levels) and were asked to point out the graphic or textual changes in the area after 30s. The eye tracker recorded ocular data, and glare perception was inquired by questionnaire. The result of T-test and Regression analysis revealed that luminance contrast was a saliency feature distinguishing visual targets and surrounding objects. The correlation between the value of luminance contrast and fixations, fixation durations on the sign is negative. Each increase in luminance contrast by one unit reduces the mean of fixations by 0.826, accompanied by a stronger feeling of glare, which indicated the strategic adaption of visual attention. The study contributed to our understanding of a new sight of lighting design in public traffic places and confirmed that lighting simulation in an immersive virtual environment can effectively analyzes visual perception.